Neuroimaging in Outpatients with Tension Type Headache: - Petramfar, Peyman; Pishgar, Sajad (Galen Medical Journal, 2015)
Background: Research into the role of neuroimaging in primary headaches such as tension type headache (TTH) is ongoing. In the present study, we aim to evaluate the ability of neuroimaging to detect potential abnormalities in patients with new onset TTH and normal neurological exam. Materials and Methods: In a prospective study, 294 cases of new onset TTH with normal neurological exam, that had neuroimaging, were selected. Imaging was evaluated for significant abnormalities. The percentage of abnormal findings in imaging was calculated. Results: 64(21.8%) patients had MRI. Of them, 21.8% of MRIs revealed abnormal findings. Meanwhile, from 238 CTs, only 0.4% showed abnormalities. Conclusion: Neuroimaging with current quality does not play an important role in management of patients with new onset TTH and normal neurological exam. [GMJ.2015;4(2):62-66]